Space Environment Data Acquisition with the Kibo Exposed Facility on the International Space Station (ISS) - T Obara (Data Science Journal, 2010)
The Space Environment Data Acquisition equipment (SEDA), which was mounted on the Exposed Facility (EF) of the Japanese Experiment Module (JEM, also known as "Kibo") on the International Space Station (ISS), was developed to measure the space environment along the orbit of the ISS. This payload module, called the SEDA-Attached Payload (AP), began to measure the space environment in August 2009. This paper reports the mission objectives, instrumentation, and current status of the SEDA-AP.